C-Myc represses the murine Nrampl promoter. (August 2002) - Bowen, H.; Biggs, T. E.; Baker, S. T.; Phillips, E.; Perry, V. H.; Mann, D. A.; Barton, C. H.
Abstract : The Nrampl (natural resistance-associated macrophage protein 1) gene modulates the growth of intracellular pathogens and encodes a divalent cation transporter within lysosomes/late endosomes of macrophages. Nrampl modulates the cytoplasmic iron pool. Wu, Polack and Dalla-Favera [(1999) Science 283, 676–679] showed reciprocal control of H-ferritin and IRP2 by c-Myc, and suggest that c-Myc regulates genes to increase cytoplasmic iron. A role for c-Myc in Nrampl regulation was evaluated. Co-transfection studies show that c-Myc represses Nrampl promoter function. Five non-canonical Myc-max binding sites (E-box) identified within the Nrampl 5′-flanking sequence are not responsible for the inhibitory effects of c-Myc on Nrampl expression. An initiator(s) adjacent to the transcriptioninitiation site is a candidate for the inhibition observed. Results are consistent with a role for Nrampl removing iron from the cytosol and antagonizing c-Myc function.